DEVELOPING A COST-EFFECTIVE MICROPREDATION PROTOCOL FOR TWO CARNATION (DIANTHUS CARYOPHYLLUS L.) VARIETIES UNDER IN VITRO CONDITIONS - Al-Mizory, Lolav Rajab; Toma, Rafail S.; Yaseen, Fareed Khalid (Science Journal of University of Zakho, 2025)
A successful attempt was made through this investigation to develop a cost-effective protocol for two varieties of carnation (Dianthus caryophyllus L.) ornamental plants named Clove Pink and Scarlet. Healthy and vigorous cultures were established by inoculating axillary buds on MS medium after a successful disinfestation process by sterilizing in 2.5% NaOCl for 10 minutes. The microshoots were multiplied by testing different benzyladenine (BA) and kinetin concentrations. Luckily, the best multiplication parameters were achieved with MS medium free of growth regulators, which will reduce the propagation costs. The higher number of shoots (11.60 shoots/ explant), leaves (59.80 leaves/ explant), and longest shoots (10.90 cm) when grown on MS medium without Plant growth regulators (PGRs), Additionally, the clove pink variety on MS medium with 1.5 mg l-1 BA and Scarlet variety grown on MS-free of PGRs respectively. A 100% percent rooting was achieved for both varieties when 1.5 mg l-1 Naphthalene acetic acid (NAA) was added to the culture media. The same NAA concentration for scarlet variety microshoots resulted in the highest number of roots (26.2 roots/explant) and the longest roots (9.0 cm). Successful acclimatization was observed by transferring the well-rooted plantlets to greenhouse conditions while putting them in peat moss